Can antipoverty programmes save lives? Quasi-experimental evidence from the Earned Income Tax Credit in the USA. Issue 8 (20th August 2020) - Muennig, Peter; Vail, Daniel; Hakes, Jahn K
Abstract : Objective: To estimate the impact of state-level supplements of the Earned Income Tax Credit (EITC) on mortality in the USA. The EITC supplements the wages of lower-income workers by providing larger returns when taxes are filed. Setting: Nationwide sample spanning 25 cohorts of people across every state in the USA. Participants: 793 000 respondents within the National Longitudinal Mortality Survey (NLMS) between 1986 and 2011, a representative sample of the USA. Intervention: State-level supplementation to the EITC programme. Some, but not all, states added EITC supplementation to varying degrees beginning in 1986 (Wisconsin) and most recently in 2015 (California). Participants who were eligible in states with supplementary programmes were compared with those who were not eligible for supplementation. Comparisons were made both before and after implementation of the supplementary programme (a difference-in-difference, intent-to-treat analysis). This quasi-experimental approach further controls for age, gender, marital status, race or ethnicity, educational attainment, income and employment status. Primary and secondary outcome measures: The primary outcome measure was survival at 10 years. Secondary outcome measures included survival at 5 years and survival to the end of the intervention period. Results: We find an association between state supplemental EITC and survival, with a HR of 0.973 (95% CI=0.951–0.996) for each US100 of EITC increase (p<0.05). Conclusion: State-level supplemental EITC may be an effective means of increasing survival in the USA.